Mechanism for Enhancing Cost Effective Budgeting for Construction Project Delivery in Anambra State - Nwachukwu, Caleb C; Okoye, Peter Izuoba (Journal of Research in Industrial Technology and Educational Studies, 2025)
The study determined Mechanisms for enhancing cost effective budgeting for construction project delivery in Anambra State. The study adopted a descriptive survey research design. Three research questions guided the study and the population comprised 101 registered builders in Anambra State. Census sampling technique was used for the study. The instrument for the study was a structured questionnaire on 4-point Likert scale. The instrument was validated by three experts who are lecturers in the Faculty of Technology and Vocational Education, Nnamdi Azikiwe University, Awka. Cronbach Alpha was utilized to determine the reliability coefficient of the instrument which yielded 0.81 which was considered good enough for the study. Mean was used to analyze the data obtained in accordance with the research questions. Findings from the study show that effective monitoring of project suppliers, effective time management among others were the mechanisms that could enhance cost effective budgeting in Anambra State. It was therefore recommended among others that construction manager should work on their spending plans and ensure that tasks are completed as at when due.